The wisdom of Sundays [compact disc, unabridged] : life-changing insights from super soul conversations - Winfrey, Oprah (Macmillan Audio, 2017)
Organized into ten chapters, each one representing a powerful step in Oprah's own spiritual journey and introduced with an intimate, personal essay by Oprah herself, this book features selections from the most meaningful conversations between Oprah and some of today's most-admired thought-leaders.